A far-IR and optical 3D view of the starburst driven superwind in NGC 2146. Issue Volume 10:Issue S309(2014) (9th February 2015) - Kreckel, Kathryn; Armus, Lee; Groves, Brent; Lyubenova, Mariya; Diaz-Santos, Tanio; Schinnerer, Eva
Abstract : Galaxy outflows are a vital mechanism in the regulation of galaxy evolution through feedback and enrichment. NGC 2146, a nearby infrared luminous galaxy (LIRG), presents evidence for outflows along the disk minor axis in all gas phases (ionized, neutral atomic and molecular). We present new far-IR Herschel imaging and spectroscopy of this galaxy from the Key Insights on Nearby Galaxies: a Far-Infrared Survey with Herschel (KINGFISH) project, as well as new optical integral field unit spectroscopy, to map the kinematics and gas excitation in the central 5 kpc and trace the dust distribution (Kreckel et al. 2014 ). We observe an increased velocity dispersion in the [OI] 62 um, [OIII] 88 um, [NII] 122 um and [CII] 158 um fine-structure lines that is spatially coincident with shocked gas above and below the disk.